STRATEGI BERTAHAN HIDUP RUMAH TANGGA PENDULANG EMAS DESA SEBERANG SUNGAI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Novriadi "; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Regency Kuantan District Singingi is located in Riau Province, Regency Kuantan Singingi rich in natural resources one of which is gold, to make panning for gold grains in this region as one of the people's livelihood to meet the needs of their daily lives.Works as a gold prospector with an income that barely is hard to imagine with such conditions how they can afford welfare of the family, educate their children, and live with the necessities of life are now all hyper-expensive, the theory used is edi sunarto, about survival strategies, and research methods used are a qualitative approach with in-depth interviews.The results showed that there are three strategies used to survive a gold prospector, namely: strategy of active, passive strategy and network strategy. Active strategy carried a gold prospector is to find another job, the family members to come to work and optimize available resources. Passive strategy carried a gold prospector that is by adopting a frugal life. Network strategy which carried gold panners are asked for help from family or neighborKeywords : Strategy Active, Passive Strategy, Network Strategy.